Intravenous branched-chain amino-acid-free solution for the treatment of metabolic decompensation episodes in Spanish pediatric patients with maple syrup urine disease - Sánchez-Pintos, Paula; Meavilla, Silvia; López-Ramos, María Goretti; García-Cazorla, Ángeles; Couce, Maria L. (Frontiers in Pediatrics, 2022)
Background. Metabolic decompensation episodes (DEs) in Maple Syrup urine disease (MSUD) result in brain accumulation of toxic branched-chain amino acids (BCAAs) and their respective branched-chain α-keto acids that could induce neuroinflammation, disturb brain bioenergetics, and alter glutamate and glutamine synthesis. These episodes require immediate intervention to prevent irreversible neurological damage. Intravenous (IV) administration of BCAA-free solution could represent a powerful alternative for emergency treatment of decompensations. Methods This paediatric series discusses the management of DEs in MSUD patients with IV BCAA-free solution, as an emergency treatment for DEs or as a prophylactic in cases requiring surgery. Clinical evolution, amino acid profile and adverse effects were evaluated. Results We evaluated the use of BCAA-free solution in 5 DEs in 5 MSUD paediatric patients, all with significantly elevated plasma leucine levels at admission (699–3296 μmol/L) and in 1 episode of risk of DE due to surgery. Leucine normalisation was achieved in all cases with resolution or improvement of clinical symptoms following IV BCAA-free solution. The duration of administration ranged from 3–20 days. Administration of IV BCAA-free solution at the beginning of a DE could reverse depletion of the amino acids that compete with BCAAs for the LAT1 transporter, and the observed depletion of alanine, despite IV alanine supplementation. No related adverse events were observed. Conclusions. Administration of standardised IV BCAA-free solution in emergency settings constitutes an important and safe alternative for the treatment of DEs in MSUD, especially in paediatric patients for whom oral or enteral treatment is not viable.